Capacitación científica y actividades de la red. Capacitación - International Center for Tropical Agriculture (International Center for Tropical Agriculture, 1986)
The methodology and achievements of training at CIAT are described. Tables indicating the training by discipline and category, and the participants trained in 1985 are included. (CIAT)